Migration of inorganic ions from the leachate of the Rio das Ostras landfill a comparison of three different configurations of protective barriers - Lacerda, Cláudia Virgínia (Waste management (New York, N.Y.), 2014)
Copyright © 2014 Elsevier Ltd. All rights reserved.